Telaah Materi dan Kesesuaian Buku Teks Cerdas Cergas Berbahasa dan Bersastra Indonesia Kelas XII dengan Kurikulum Merdeka - Firmansyah, Arif; Ayun, Tazkiah Qurotul (Fakultas Sastra Universitas Muslim Indonesia, 2025)
The purpose of this study is to find the suitability of the material regarding the Smart Healthy Indonesian Language and Literature Class XII textbook in the Independent Curriculum. Specifically, this study aims to describe and analyze the aspects of (1) the conformity of materials with learning outcomes in the Independent Curriculum; (2) integration of pancasila Student Profile Values; and (3) accuracy of the material. The research methods used are qualitative descriptive methods and data collection techniques with documentation studies collected through analysis of textbook content, which includes themes and materials. The collected data is analyzed by reducing information based on curriculum themes and indicators. Based on the results of the research, it can be concluded that this book is in accordance with the standards of the Independent Curriculum, supports the development of literacy, critical thinking skills, creativity, and character of students, as well as comprehensively integrates the values of the Pancasila Student Profile.